Effects of vitamin D supplementation in endometriosis: a systematic review - Dimitrios Rafail Kalaitzopoulos; Nicolas Samartzis; Angelos Daniilidis; Brigitte Leeners; Sofia Makieva; Konstantinos Nirgianakis; Ioannis Dedes; Julian Matthias Metzler; Patrick Imesch; Ioannis G. Lempesis (BMC, 2022)
Abstract Background There is a growing body of human, animal and in vitro studies on vitamin D (vit D) substitution in endometriosis. The aim of this systematic review is to critically appraise and qualitatively synthesize the results of the available studies that examine the supplementation of vit D for endometriosis treatment. Methods A systematic search of the literature was conducted in four electronic databases (Medline, Cochrane, Scopus, Embase) and grey literature for original research articles on humans, animals and in vitro models published in any language. Results Four human studies, four animal studies and four in vitro studies were included. Quantitative synthesis of human studies showed no significant effect of vit D intake for dysmenorrhea (2 studies, 44 vit D vs 44 placebo, mean -0.71, 95% CI -1.94, 0.51) and non-cyclic pelvic pain (2 studies, 42 vit D vs 38 placebo, mean 0.34, 95% CI -0.02, 0.71). Regarding reproductive outcomes in women with endometriosis after in vitro fertilization, the only available study showed no differences between women taking vit D and women taking placebo. Three of the four included animal studies showed regression of endometriotic implants when treated with vit D. The in vitro studies demonstrated that vit D decreases invasion and proliferation of endometriotic lesions without affecting apoptosis. Conclusions Although in vitro and animal studies suggest regression of the endometriotic implants and decrease of invasion and proliferation after vit D supplementation, this was not reflected in the results of the meta-analysis, which showed no benefit of vit D supplementation in patients with endometriosis and dysmenorrhea or non-cyclic pelvic pain as well as on the outcome of IVF treatment. However, given the heterogeneity and the diversity of the available studies, more research is required to shed light on the role of vit D supplementation in women with endometriosis.